State‐of‐the‐Art Report in Web‐based Visualization. (4th July 2016) - Mwalongo, F.; Krone, M.; Reina, G.; Ertl, T.
Abstract: In this report, we review the current state of the art of web‐based visualization applications. Recently, an increasing number of web‐based visualization applications have emerged. This is due to the fact that new technologies offered by modern browsers greatly increased the capabilities for visualizations on the web. We first review these technical aspects that are enabling this development. This includes not only improvements for local rendering like WebGL and HTML5, but also infrastructures like grid or cloud computing platforms. Another important factor is the transfer of data between the server and the client. Therefore, we also discuss advances in this field, for example methods to reduce bandwidth requirements like compression and other optimizations such as progressive rendering and streaming. After establishing these technical foundations, we review existing web‐based visualization applications and prototypes from various application domains. Furthermore, we propose a classification of these web‐based applications based on the technologies and algorithms they employ. Finally, we also discuss promising application areas that would benefit from web‐based visualization and assess their feasibility based on the existing approaches.